(untitled) (Rudarsko-geološko-naftni zbornik, 2023)
The lining system, used in tunnel boring machines, is made of precast concrete segments. The use of steel fibers in this kind of support system can not only decrease production time and costs but also can improve compressive, tensile as well as flexural behaviors. A study has been carried out to examine the mechanical properties of segments in the Tabriz metro line-2 project using three types of steel fibers: 3D, 4D, and 5D. Various experiments were investigated to monitor the workability of Steel Fiber Reinforced Concrete (SFRC) under various loads. The results confirmed an improvement in the specimens’ mechanical properties because of these types of steel fibers. 5D, 4D, and 3D fibers provided the greatest effect on the tensile and flexural strength of steel fiber-reinforced concrete, respectively. The 28-day compressive, tensile, and flexural strengths of the specimens are incremented by 13%, 68%, and 154%, respectively. In addition, by conducting tests on the orientation of steel fibers, placing the fibers perpendicular to the load can improve the compressive strength of concrete by almost 18%.